IMPLEMENTASI PROGRAM RUMAH PADAT KARYA DALAM RANGKA MENGURANGI ANGKA KEMISKINAN KECAMATAN WONOCOLO KOTA SURABAYA PERIODE 2022-2023 - Maharima, Amara Nilla; -, supratiwi -; -, Yuwanto - (Journal of Politic and Government Studies, 2024)
The Rumah Padat Karya Program is one of the programs approved by the Surabaya City Government as a form of effort to deal with the increase in poverty and unemployment rates due to the impact of Covid-19. Wonocolo is one of the sub-districts that has a labor intensive house with several businesses in it. The implementation of Rumah Padat Karya Program encourages research to obtain adequate information related to the implementation of the Rumah Padat Karya Program. The aim of this research is to analyze the implementation of the Rumah Padat Karya Program in Kecamatan Wonocolo, Surabaya City, as a poverty alleviation program and reduce unemployment rates and to analyze the driving and inhibiting factors of program implementation. In this research, the analysis related to program implementation uses an implementation theory approach with four factors as conditions for the success of program implementation. This research uses descriptive qualitative research methods as a tool in solving the problems raised, using interview techniques, observation and literature study. The research results show that the implementation of the Rumah Padat Karya program in Wonocolo District has gone quite well, assessed by the four factors of implementation going well.